Association between parent-perceived neighborhood support on food insufficiency and public benefit participation among US children - Claire E. Branley; Mary R. Lee; Sharina Person; Kurt Hager; Stephenie C. Lemon (Preventive Medicine Reports)
Objectives: Food insufficiency leads to significant negative health outcomes among children. A neighborhood's social environment (including social cohesion and support) could be associated with participation in federal nutrition programs that reduce food insufficiency through sharing of information related to how to enroll. We sought to examine the association of parent-perceived neighborhood support with food insufficiency and participation in the Supplemental Nutrition Assistance Program (SNAP) and the Special Supplemental Nutrition Program for Women, Infants, and Children (WIC) among US children. Methods: Cross-sectional data from the 2022 National Survey of Children's Health, a nationally representative survey of US children aged 0–17, were used (n = 49,907). Weighted ordinal logistic regression models estimated the adjusted odds ratio (aOR) for the relationship between caregiver-perceived neighborhood support and food insufficiency and weighted logistic regression models for the association between neighborhood support and SNAP and WIC participation. Results: In 2022, 44 % of children lived in non-supportive neighborhoods. After controlling for covariates and accounting for sampling weights, children in non-supportive neighborhoods had 2.41 times the odds of food insufficiency (aOR: 2.39; 95 % CI: 2.19–2.65) and 1.18 times the odds of participating in SNAP (95 % CI 1.01–1.37), but there was no significant association with WIC participation (aOR: 1.04, 95 % CI 0.84–1.29). Conclusions: Despite low neighborhood social support being significantly associated with food insufficiency, it is associated with only slightly higher odds of participation in SNAP and is not associated with WIC participation. Further research is needed to understand whether social networks can be leveraged to improve uptake of these programs.